2020
DOI: 10.3389/fnhum.2019.00455
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Measurements Through the Touch of Materials Surfaces

Abstract: The emotion generated by the touch of materials is studied via a protocol based on blind assessment of various stimuli. The human emotional reaction felt toward a material is estimated through (i) explicit measurements, using a questionnaire collecting valence and intensity, and (ii) implicit measurements of the activity of the autonomic nervous system, via a pupillometry equipment. A panel of 25 university students (13 women, 12 men), aged from 18 to 27, tested blind twelve materials such as polymers, sandpap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 118 publications
2
23
0
Order By: Relevance
“…All studies indicated a positive correlation between stimuli perception and pupil dilation ( Table 2 ). As shown in Figure 3 , while Bertheaux et al ( 2020 ) found that neutral materials lead to a lower pupil dilation than materials with high emotional intensity, independently of their valence (being pleasant or unpleasant), Van Hooijdonk et al ( 2019 ) associated the difference in the pupil dilation only with the stimulus intensity, not subjective pleasantness. The four go/no-go tasks (Lee and Margolis, 2016 ; Schriver et al, 2018 , 2020 ; Mückschel et al, 2020 ) and the 2AFC task (Ganea et al, 2020 ) found a significantly broader pupil dilation for go trials than no-go ones.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…All studies indicated a positive correlation between stimuli perception and pupil dilation ( Table 2 ). As shown in Figure 3 , while Bertheaux et al ( 2020 ) found that neutral materials lead to a lower pupil dilation than materials with high emotional intensity, independently of their valence (being pleasant or unpleasant), Van Hooijdonk et al ( 2019 ) associated the difference in the pupil dilation only with the stimulus intensity, not subjective pleasantness. The four go/no-go tasks (Lee and Margolis, 2016 ; Schriver et al, 2018 , 2020 ; Mückschel et al, 2020 ) and the 2AFC task (Ganea et al, 2020 ) found a significantly broader pupil dilation for go trials than no-go ones.…”
Section: Resultsmentioning
confidence: 97%
“…As Table 2 and Figure 3 show, the nine studies were conducted between 1996 and 2020. Three used human subjects (two with adults and one with adolescents) (Van Hooijdonk et al, 2019 ; Bertheaux et al, 2020 ; Mückschel et al, 2020 ), one wild mice (Lee and Margolis, 2016 ), two with C57BL6J mice (Ganea et al, 2020 ; Lee et al, 2020 ), two albino rats (Schriver et al, 2018 , 2020 ), and one juvenile male Japanese monkeys ( Macaca fuscata ) (Iriki et al, 1996 ). Four studies used go/no-go tasks (Lee and Margolis, 2016 ; Schriver et al, 2018 , 2020 ; Mückschel et al, 2020 ), one a vibration detection task (Lee et al, 2020 ), one a two-alternative forced choice (2AFC) task (Ganea et al, 2020 ), one used a passive task (Iriki et al, 1996 ), and two discrimination of affective touch tasks (Van Hooijdonk et al, 2019 ; Bertheaux et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations